2004
DOI: 10.1097/01.rhu.0000141831.40350.91
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Functional Electrostimulation on Pain, Muscular Strength, and Functional Capacity in Patients With Osteoarthritis of the Knee

Abstract: FES merits a larger placebo-controlled study as it may prove to be useful patients with OA of the knee; the combination with exercise was helpful in improving muscle strength. This technique may be considered in patients who are unable to carry out physical activity due to health problems or in those who are not interested in physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 13 publications
2
60
1
Order By: Relevance
“…Durmus et al 26 found increments of about 35% in the one maximal repetition test after 5 weekly sessions of NMES training during 4 weeks, while Rosemffet et al 25 did not observe any significant gain in isometric force after 8 weeks of training with three NMES sessions per week. These different outcomes with apparently similar NMES stimulation training protocols might be associated with the methods for evaluating maximal strength, to the level of impairment of the OA patients, or the detailed parameters chosen for the NMES training programs (current, duration, frequency, etc.).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Durmus et al 26 found increments of about 35% in the one maximal repetition test after 5 weekly sessions of NMES training during 4 weeks, while Rosemffet et al 25 did not observe any significant gain in isometric force after 8 weeks of training with three NMES sessions per week. These different outcomes with apparently similar NMES stimulation training protocols might be associated with the methods for evaluating maximal strength, to the level of impairment of the OA patients, or the detailed parameters chosen for the NMES training programs (current, duration, frequency, etc.).…”
Section: Discussionmentioning
confidence: 96%
“…34 Specifically, OA patients have shown a significant decrease in pain, [23][24][25][26][27][28] a reduction in joint stiffness, 26,27 an increase in joint range of motion, 28 and an improvement in functional performance 23,26 following NMES training. Although we cannot establish a direct causative association between muscle strength and health status, stronger knee extensor muscles are thought to decrease impact forces at the knee joint, 16,17 and might reduce the mechanical stimuli for pain, 18 thereby relieving the pain symptoms of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of researches considered several aspects related to muscle function, such as strength and aerobic capacity as well as other clinical aspects, such as pain, stifness, range of motion of the knee, and WOMAC in patients with OA [14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Its main objective is to increase the musculature force that is inhibited due to joint pain, through the artificial generation of muscle contractions. [9][10][11][12][13][14] However, there is little evidence describing the use of NMES and its relation to an improvement in neuromuscular and mechanical properties in elderly patients with OA. Similarly, the effects of NMES training on the root mean square (RMS)/torque ratio have not yet been fully explained.…”
Section: Introductionmentioning
confidence: 99%